Evaluating and implementing The CONNECT Program—A group-based telehealth intervention to reduce social isolation, loneliness, and mental health symptoms in adults 55+ vs routine community programming: Study protocol for a randomized controlled trial - Kira Kudar; Georgia Gopinath; Alex Ross; Robert Balshaw; Edwin Chau; Inga Christianson; Lesley Koven; Corey S. Mackenzie; Stacey Miller; Nancy Newall; Lyne Ouellet; Kathryn Sibley; et al. (PLoS ONE, 2025)
Background The population of adults aged 55 years and older in Canada is growing steadily to be one of the largest demographic groups, creating an aging society. Adults 55 + are facing dynamic changes in employment and finances, relationships, living situation, and health, which may contribute to increased psychosocial and psychological challenges, including social isolation, loneliness, depression, and anxiety. Importantly, when adults 55 + need mental health support, they are less likely to access this support compared to other demographics. When supports are grounded in the community and are available through telephone and video-conferencing, access can be improved. Developed in partnership with community organizations, The CONNECT Program is designed to improve the psychosocial well-being of older adults, focusing on psychological flexibility, and in this randomized controlled trial will be compared against routine community-based programming across Canada. Methods This randomized crossover trial is embedded within a type 1 hybrid implementation-effectiveness design across four Canadian provinces. Adults aged 55+ with self-reported experiences of loneliness, social isolation, and/or mental health challenges are randomly assigned to begin with either the intervention (The CONNECT Program) or community-based programming, then cross over to the other condition. The CONNECT Program is a six-week, group-based telehealth intervention grounded in Acceptance and Commitment Therapy, self-compassion, theories of successful aging delivered via telephone or videoconference. The primary outcome is psychological flexibility; secondary outcomes include loneliness, social isolation, emotional support, anxiety, depression, and mental health literacy. Implementation outcomes will be assessed using the Proctor Framework. Discussion The CONNECT Program is a novel community-based mental health intervention addressing the needs of adults 55 + who experience isolation, loneliness and mental health challenges. The results of this trial will strengthen support for a scalable mental health support for Canadians 55+ in a time of high need to promote health in later life. Trial registration The trial was registered on ClinicalTrials.gov: NCT07107906, 08/05/2025, https://clinicaltrials.gov/study/NCT07107906 .